Aboriginal men fishing at night for crabs and fish, using a torch made out of paperbark tree, South Goulburn Island, Northern Territory, August 1952 - Poignant, Axel, 1906-1986. (1952)
"Fishing at night. Party of men fishing at night in shallows for crabs and small fish, by light of torch made by firing bundles of bark from paperbark tree. (these special torches are called iradj)..."--Label on reverse of print version.
Title devised by cataloguer based on information from label attached to the print version.
Part of the collection: Photographs of Aboriginal life and customs, including Goulburn Island South, Liverpool River, Melville Island, Bathurst Island, Milingimbi, Arnhem Land and Elcho Island districts.
"Negative no.: AL 84.12"
Digital master available
Also available as a print, located in Album 1128.
Purchased from Dr. Roslyn Poignant, 2008.
Keywords: Aboriginal Australians -- Northern Territory -- Goulburn Island -- Photographs; Aboriginal Australians -- Northern Territory -- Goulburn Island -- Social life and customs -- Photographs; Fishing nets -- Northern Territory -- Goulburn Island -- Photographs; Goulburn Island (N.T.) -- Photographs